EXPERIENCE OF NURSE ASSOSIATE TO IMPLEMENT TRIAGE IN EMERGENCY ROOM INSTALLATION - Febrina, Wiwit; Sholehat, Indah Okzana (Jurnal Endurance, 2018)
Triageis a system of in the Emergency Room aims to select or classify all patients who need the help and assign priority handling. A study on the phenomena that occur on experience in performing triage nurse. Researchers use qualitative research design with phenomenology approach. The research was conducted at Emergency Installation of Dr. Achmad Mochtar Bukittinggi. Population and sample in this research is numbered 3 participants, the study was obtained by purposive sampling.. Instrument Participant of the research is the nurse in the room of the Emergency Room Installation, the research in this research is the researcher himself. The study of 3 participants gained six themes, namely: (1) skill Technically nurse triage, (2) the principle of triage, (3) the ability of sorting patients is still not effective, (4) infrastructure, (5) the impact of doing mistakes triage and (6) solutions for patient safety. Hospital and emergency room is recommended to add special training triage nurse triage, is expected to provide motivation for the triage nurse and triage nurse are expected to be in the room triage to be able to do sorting.Triage adalah suatu proses yang dilakukan di Instalasi Gawat Darurat . Tujuan Triage adalah mengelompokkan atau mengkategorikan semua pasien yang butuh pertolongan untuk menetapkan prioritas penanganannya. Penelitian ini dilakukan untuk mengetahui fenomena-fenomena yang terjadi mengenai pengalaman perawat dalam melaksanakan triage. Penelitian ini merupakan penelitian kualitatif dengan pendekatan fenomenologi yang dilakukan di Instalasi Gawat Darurat  RSUD Dr. Achmad Mochtar Bukittinggi. Populasi dan sampel dalam penelitian ini yaitu berjumlah 3 orang partisipan, penelitian tersebut diperoleh dengan teknik purposive sampling.. Instrumen Partisipan penelitian adalah perawat pelaksana diruangan Instalasi Gawat Darurat, penelitian dalam penelitian ini adalah peneliti sendiri. Hasil penelitian terhadap 3 partisipan diperoleh 6 tema, yaitu: (1) keterampilan teknikal perawat triage, (2) prinsip triage, (3) kemampuan dalam pemilahan pasien masih belum efektif, (4) sarana prasarana, (5) dampak dalam melakukan kesalahan triage, dan (6) solusi untuk keselamatan pasien. Rumah sakit dan Instalasi Gawat Darurat disarankan untuk menambahkan pelatihan khusus triage bagi perawat triage, di harapkan dapat memberikam motivasi bagi para perawat triage, serta  perawat triage diharapkan dapat selalu berada di ruang triage untuk dapat melakukan pemilahan.